2019
DOI: 10.1097/wnr.0000000000001262
|View full text |Cite
|
Sign up to set email alerts
|

Impaired hippocampal functional connectivity in patients with drug resistant, generalized tonic-clonic seizures

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…In the present study, it is worth noting that the average VMHC values in the bilateral HF and LTC were significantly correlated with the epilepsy duration. Previous studies have confirmed that epilepsy duration is one of the main clinical factors affecting a patient’s functional organization ( Wang et al, 2011 , 2018 , 2019b ; Liu et al, 2017 ). In these previous studies, the FC between the regions within the DMN or between the DMN and other subnetworks of the brain showed negative correlations with the epilepsy duration.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In the present study, it is worth noting that the average VMHC values in the bilateral HF and LTC were significantly correlated with the epilepsy duration. Previous studies have confirmed that epilepsy duration is one of the main clinical factors affecting a patient’s functional organization ( Wang et al, 2011 , 2018 , 2019b ; Liu et al, 2017 ). In these previous studies, the FC between the regions within the DMN or between the DMN and other subnetworks of the brain showed negative correlations with the epilepsy duration.…”
Section: Discussionmentioning
confidence: 84%
“…In the past few years, investigating the functional interactions between regions has become a powerful tool to explore the human brain. In a resting state fMRI study, the disruption of FC networks in GTCS has been reported ( Wang et al, 2011 , 2019b ; Liu et al, 2017 ; Parsons et al, 2020 ). Connectivity changes in a number of brain regions involved the HP, thalamus, insula, temporal cortex, cerebellum, precuneus, and medial prefrontal cortex.…”
Section: Discussionmentioning
confidence: 98%
“…The same group found significantly reduced default mode network connectivity and cerebellar resting‐state functional connectivity among patients with valproate‐resistant IGE 88,89 . Hippocampal functional connectivity was found to be impaired and negatively correlated with epilepsy duration in drug‐resistant generalized tonic–clonic seizures in IGE, whereas drug‐responsive patients demonstrated compensatory improvement in hippocampal functional connectivity on follow‐up 90 . However, a recent study using the graph theory on resting state fMRI data did not find significant differences in network topology between drug‐resistant and responsive IGE 91 …”
Section: Exploring Functional Connectivity and Epileptic Networkmentioning
confidence: 87%
“…Some studies have found no significant difference in the subcortical structure volume of IGE-GTCS patients compared with that of normal controls (NCs) ( Bernasconi et al, 2003 ; Natsume et al, 2003 ; Seeck et al, 2004 ; Ozturk et al, 2020 ). Some functional MRI studies complemented these findings, indicating connectome anomalies in the thalamus and hippocampus ( Wang et al, 2019a , b ). Despite the contribution of these findings to localizing anomalies in this disease, there is limited insight into the specific clinical value of the abnormality of subcortical nuclei.…”
Section: Introductionmentioning
confidence: 77%